Respuesta :

This is how it should look
Ver imagen pxg5022

Answer:

The graph of equation is shown in figure 1.

Step-by-step explanation:

Consider the provided equation.

[tex]y=2x^2[/tex]

Now draw the graph of the equation.

Substitute x = 0 in the provided equation.

[tex]y=2(0)^2[/tex]

[tex]y=0[/tex]

Substitute x = 1 in the provided equation.

[tex]y=2(1)^2[/tex]

[tex]y=2[/tex]

Substitute x = -1 in the provided equation.

[tex]y=2(-1)^2[/tex]

[tex]y=2[/tex]

Substitute x = 2 in the provided equation.

[tex]y=2(2)^2[/tex]

[tex]y=2(4)[/tex]

[tex]y=8[/tex]

Substitute x = -2 in the provided equation.

[tex]y=2(-2)^2[/tex]

[tex]y=2(4)[/tex]

[tex]y=8[/tex]

Now draw the table as shown:

 x       -2     -1     0     1     2

f(x)      8      2     0     1     8

Hence, the graph of equation is shown in figure 1.

Ver imagen FelisFelis